2021
DOI: 10.1016/j.celrep.2020.108677
|View full text |Cite
|
Sign up to set email alerts
|

Nod1 promotes colorectal carcinogenesis by regulating the immunosuppressive functions of tumor-infiltrating myeloid cells

Abstract: Highlights d Nod1 affects MDSC expansion and alternative reprogramming of macrophages d Nod1-mediated autophagy regulates arginase-1 levels in macrophages and MDSCs d Myeloid-specific Nod1 signaling modulates T cell suppression via arginase-1 d Myeloid Nod1 shapes the tumor microenvironment to promote colorectal cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 88 publications
0
47
0
Order By: Relevance
“…TAMs inhibit T cell proliferation through arginine metabolism regulated by arginase1, iNOS, and oxygen or nitrogen radicals [29,91,92]. TAMs directly inhibit CD8 + T cell cytotoxicity through myeloid-specific NOD1 signaling via the release of arginase 1, which promotes immunosuppression and the tumor-permissible tissue microenvironment in CRC development [17,93]. TAMs produce IL-10, which can suppress CD8 + T cell activation by decreasing CD8 protein and T cell receptor colocalization [94].…”
Section: Tams Regulate Immunity In Tme Of Crcmentioning
confidence: 99%
“…TAMs inhibit T cell proliferation through arginine metabolism regulated by arginase1, iNOS, and oxygen or nitrogen radicals [29,91,92]. TAMs directly inhibit CD8 + T cell cytotoxicity through myeloid-specific NOD1 signaling via the release of arginase 1, which promotes immunosuppression and the tumor-permissible tissue microenvironment in CRC development [17,93]. TAMs produce IL-10, which can suppress CD8 + T cell activation by decreasing CD8 protein and T cell receptor colocalization [94].…”
Section: Tams Regulate Immunity In Tme Of Crcmentioning
confidence: 99%
“…They exist in almost all body fluids and part of a new type of communication system between cells. The system can carry various cellular molecules that can regulate the physiological morphology of cells and is also closely related to the occurrence of various diseases [4]. Studies have found that tumor derived exosomes can directly inhibit the proliferation of CD8+ T cells, the production of cytokines and cytotoxicity [5].…”
Section: Introductionmentioning
confidence: 99%
“…Except for the microorganisms and metabolites mentioned above, other less investigated bacteria, fungi, archaea, viruses, and metabolites synthesized de novo by gut microbes also influence the host (reviewed elsewhere [10,13]). To give an example, Nod1 stimulation by bacterial peptidoglycan-derived muramyl peptides (MPs) induced monocytic MDSCs infiltration and TAM, which drove carcinogenesis in AOM/DSS treated mice and Apc Min/+ mice [159]. The latest studies uncovered that Streptococcus thermophilus and Faecalibaculum rodentium exerted anti-cancer effects by their metabolites, which reminds us that the role of the bacteria and their metabolites strongly reduced during carcinogenesis is worth exploring to seek therapy opportunity [32,160].…”
Section: Discussionmentioning
confidence: 99%